Towards Poverty Reduction and Sustainability in West African Countries: Role of Entrepreneurial Empowerment - Olubiyi Timilehin Olasoji; Kolade Akinpelu Ayobami; Bamidele Comfort Olaitan (Jurnal sosial dan sains, 2024)
Poverty reduction in Africa is one of the main issues African governments and their financial partners face. Over the years, billions of U.S. funds have been invested to aid African countries in fighting pervasive Poverty. Despite efforts to implement changes and promote growth initiatives, it is obvious that expected outcomes have not been met yet. This study examined the Impact of Entrepreneurial Empowerment on Poverty Reduction and Sustainability in West African Countries with empirical evidence from the Tony Elumelu Foundation. The study's purpose is to assess how the TEF Entrepreneurship Program contributes to poverty reduction in West African countries and adopts an ex-post research design from the TEF financial report expenses on entrepreneurship programs in West African countries. The study finds that TEF entrepreneurship programs contribute to poverty reduction in West African countries by just 28% which is quite impressive. These findings also highlight the significant growing expenses. In developing West African nations, the value of generous organizations that help facilitate the success of those businesses contributes to progress toward the global SDGs through the trend. The study therefore recommends that the analyses should provide strong evidence and validation that these TEF Program pillars are critical for entrepreneurial success and should therefore be retained and continue to be mandatory pillars of the poverty reduction Program.